Convict Transportation from Britain and Ireland 1615–1870 - Maxwell-Stewart, Hamish (History compass, 2010)
In 1787, the First Fleet was dispatched from the British Isles to find a penal settlement at Botany Bay, Australia. By this time, the British government had already experimented with convict transportation for over 160 years. The aim of this article is to place the history of transportation to Australia within the context of the wider flow of convict labour from the British Isles in the period 1615 to 1870. Using data from a range of sources it attempts to chart and explain fluctuations in the number of convicts transported over time. It also seeks to explore how the integration of convict labour within the transatlantic market in unfree labour-shaped British penal policy in the long-run. Such an analysis is useful in explaining the differing impacts that transportation had on the prisoners who experienced it and the intensity with which it was opposed in the 19th century by the British anti-slavery movement. Geographically the article explores these issues in relation to transportation to the New World (especially Barbados, Jamaica, Maryland and Virginia), West Africa, New South Wales, Van Diemen’s Land (Tasmania), Western Australia, Bermuda and Gibraltar.